Coronary Artery Calcification in Hemophilia A: No Evidence for a Protective Effect of Factor VIII Deficiency on Atherosclerosis - Tuinenburg, Attie; Rutten, Annemarieke; Kavousi, Maryam; Leebeek, Frank W.G.; Ypma, Paula F.; Laros-van Gorkom, Britta A.P.; Nijziel, Marten R.; Kamphuisen, Pieter W.; Mauser-Bunschoten, Eveline P.; Roosendaal, Goris; Biesma, Douwe H.; van der Lugt, Aad; et al. (Arteriosclerosis, thrombosis, and vascular biology, 2012)
OBJECTIVE—Ischemic heart disease mortality is lower in hemophilia patients than in the general male population. As coagulation plays a role in the inflammatory pathways involved in atherogenesis, we investigated whether the clotting factor deficiency protects hemophilia patients from developing atherosclerosis. METHODS AND RESULTS—Coronary artery calcification, measured with multidetector-row computed tomography, was compared between 42 men, ≥59 years, with severe or moderate hemophilia A, and 613 nonhemophilic men from the Rotterdam Study, a prospective population-based study. None of the study subjects were HIV infected or had a history of cardiovascular disease. Coronary artery calcification was quantified by calculating the Agatston score and calcification mass. Data were analyzed using linear regression. Mean difference (β) of the natural log–transformed Agatston score between men with and without hemophilia was 0.141 (95% CI −0.602 to 0.885, P=0.709). Results did not change after adjustment for age, body mass index, hypercholesterolemia, hypertension, and use of antidiabetic medication (β=0.525, 95% CI −0.202 to 1.252, P=0.157). Comparable results were found for calcification mass. CONCLUSION—The extent of coronary artery atherosclerosis is comparable between elderly men with and without hemophilia. Results from this study underline the importance of screening and treating atherosclerosis risk factors in hemophilia patients.